Young children's exposure to phenols in the home: Associations between house dust, hand wipes, silicone wristbands, and urinary biomarkers. (February 2021) - Levasseur, Jessica L.; Hammel, Stephanie C.; Hoffman, Kate; Phillips, Allison L.; Zhang, Sharon; Ye, Xiaoyun; Calafat, Antonia M.; Webster, Thomas F.; Stapleton, Heather M.
Highlights: Paired hand wipe, wristband, house dust and urine samples were analyzed for phenols. Exposure matrices and urinary biomarkers were positively correlated. Triclosan in dust, wristbands and hand wipes was correlated with urinary biomarkers. Lotion use was associated with ethyl, methyl, and propylparaben biomarkers. Abstract: Background: Environmental phenols, such as parabens, bisphenol A, and triclosan, are ubiquitous in indoor environments because of their use in packaging, plastics, personal care products, and as anti-microbials. The primary pathways of exposure, as well as habits and behaviors that may lead to greater exposure, are still unclear. Objectives: Herein, we investigate the relationships between phenols found in residential environments by comparing levels in paired samples of house dust and hand wipes with children's urine. In addition, phenols were analyzed in a novel exposure tool, the silicone wristbands, to investigate which external matrix best correlates with individual exposure based on urinary phenol biomarkers. Methods: Children aged 3–6 years in central North Carolina, United States, provided paired hand wipe (n = 202), wristband (n = 76), and spot urine samples (n = 180), while legal guardians completed questionnaires on habits and behaviors. House dust samples (n = 186) were collected from the main living area during home visits completed between 2014 and 2016. Results: Environmental phenols were detected frequently in all matrices investigated. Ethyl, methyl, and propylparaben levels observed in hand wipes, dust, and on wristbands were significantly correlated to their associated urinary biomarkers. In addition, intra-paraben correlations were noted, with biomarkers of ethyl, methyl, and propylparabens generally positively and significantly correlated, which suggests co-application of parabens in products. Triclosan levels in dust were positive and significantly correlated with levels in hand wipes and wristbands and with urinary concentrations, suggesting non-personal care product sources may be important in children's overall triclosan exposure. Generally, chemicals on wristbands were more highly correlated with urinary biomarkers than with chemicals in hand wipes or house dust. In addition, more frequent lotion use was positively associated with urinary concentrations of paraben biomarkers. Conclusions: Our results suggest that the home environment is an important source of exposure which has been under-investigated for some environmental phenols (e.g., triclosan in house dust). Associations between wristbands and biomarkers of exposure, which were stronger than for hand wipes and house dust, suggest that silicone wristbands may provide a suitable exposure assessment tool for some phenols.